Modelling and dynamics of intramammary infections caused by Corynebacterium species - Rachah, Amira; Dalen, Gunnar; Reksen, Olav; Norstebo, Havard; Barlow, John W. (2017 7th International Conference on Modeling, Simulation, and Applied Optimization (ICMSAO), 2017)
We present a deterministic mathematical model that describes the transmission dynamics of intramammary infections (IMI) caused by Corynebacterium spp. (Corynebacterium species) in lactating dairy herds. Longitudinal, quantitative, dynamic models are likely to be valuable for predicting infections outbreak risk, quantify the effectiveness of response tactics and performing response planning. Previous investigations on IMI have considered the transmission of several bacterial pathogens, but not Corynebacterium spp., in modelling investigations. We have established a new Corynebacterium spp. S n IS w compartmental model subject on appropriate unknown parameters that we estimated by using a deterministic approach, based on real data fitting procedure. The real data, from which the parameters of the model are estimated, were obtained in a field trial conducted in a New York dairy herd (US).